Modulation of Intestinal Histology and Immune Functions Using Different Level of Salvia Indica Supplementations with Stocking Density in Local Quails - Haval Ismail Aziz; Rebin Aswad Mirza; Karwan Yaseen Karim; Payam Sadiq Sabir; Ali Mala Khidhr (Zanco Journal of Pure and Applied Sciences, 2024)
Under the direction of Salahaddin University in Erbil's College of Agricultural Engineering Sciences, study was carried out to investigate how local quail performed biochemically, histologically, and immune-wise when varied levels of Salvia indica (SI) additive were added at high stocking density. For a 42-day trial, 216 one-week-old local quails were divided into four treatments at random, with three replicates for each treatment, in cages measuring 60 by 30 by 25 centimeters. The following was the design of the feed treatments: Positive control (12 birds/replicate), Negative control 20 birds per replicate at a high stocking density, 20 birds per replicate plus 0.2% of SI additive, and 20 birds per replicate plus 0.4% of SI additive. When compared to a negative control, the results indicated that 0.4% SI supplements with high stocking density produced the best live body weight and weight gain. When compared to positive and negative controls, the cholesterol level of female quails considerably (P<0.05) decreased in both SI with high stocking density; however, no significant variations were seen with either of the SI additives with high stoking density. Furthermore, when compared to the positive control, the LDL content in female quails was considerably (P<0.05) reduced by both supplements of SI with high stocking density and negative control. When treated with SI, the height of the jejunum villus was significantly (P<0.05) higher than when treated with both positive and negative controls. The size of Fabricius follicles was significantly (P<0.05) enhanced by the addition of SI treatments, but no significant difference was seen between the two SI additives with high stocking density. In summary, adding Salvia indica to a diet with high stocking density enhanced the quail population's biochemical markers, immunological response, and jejunum histology.